2006
DOI: 10.21273/hortsci.41.5.1200
|View full text |Cite
|
Sign up to set email alerts
|

Soilless Media and Containers for Greenhouse Production of `Galia' Type Muskmelon

Abstract: In the spring of 2001 and 2002, different combinations of media (coarse perlite, medium perlite, and pine bark) and containers (polyethylene bags and plastic pots) were used for hydroponic production of `Galia' muskmelons (Cucumis melo L.) to determine their effect on fruit yield and quality, and their influence on costs of production. Marketable yields obtained for `Gal-152' in the spring 2001 and 2002 were 25.5 kg·m–2 and 39.0 kg·m–2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
(46 reference statements)
0
16
0
5
Order By: Relevance
“…No differences in [6]-gingerol were observed according to the type growth media. Investigation by Rodriguez et al (2006) on the effect of different substrates for hydroponic production of 'Galia' muskmelons (Cucumis melo L.) revealed that fruit quality and composition were not affected by substrate. Others studies also had showed that rising concentration of electric conductivity (EC) of nutrient solution and nutrient solution composition can caused increase in total soluble solids, organic acids and plant secondary metabolites for tomatoes (Petersen et al, 1998), sweet pepper and cucumber (Trajkova et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…No differences in [6]-gingerol were observed according to the type growth media. Investigation by Rodriguez et al (2006) on the effect of different substrates for hydroponic production of 'Galia' muskmelons (Cucumis melo L.) revealed that fruit quality and composition were not affected by substrate. Others studies also had showed that rising concentration of electric conductivity (EC) of nutrient solution and nutrient solution composition can caused increase in total soluble solids, organic acids and plant secondary metabolites for tomatoes (Petersen et al, 1998), sweet pepper and cucumber (Trajkova et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the excessively high EC levels in the recycled solution on melon fruit setting could not be assessed in the present study, as only two fruits were left to mature in each plant, following common practices in early greenhouse crops of “Galia” melon ( Rodriguez et al, 2006). As reported by Mavrogiannopoulos et al (1999), moderately high salinity levels do not significantly affect the number of fruits per plant in melon, and mean fruit weight is more sensitive to salinity than the fruit number per plant.…”
Section: Discussionmentioning
confidence: 99%
“…White spruce and fir bark alone or mixed with low-grade peat showed high potential for greenhouse tomato production and represented an environmentally sound alternative to rockwool [136]. Moreover, pine bark can be successfully used as a stand-alone substrate for the cultivation of vegetables, such as bell pepper, cucumbers, and muskmelons [137][138][139]. An economic analysis determined that pine bark was nearly one-eighth the cost of perlite and could be reused for several consecutive crops, resulting in reduced production costs and greater profits.…”
Section: Greenhouse Vegetable Productionmentioning
confidence: 99%